2020
DOI: 10.1039/d0cc01004a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of microRNA using a bismuthene-enabled fluorescence quenching biosensor

Abstract: A novel ultrathin bismuthene-based sensing platform for microRNA (miRNA)-specific detection has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…The limit of detection (LOD) was estimated to be 0.2 pM according to the 3σ rule, which was comparable to some previously reported fluorescence assays for miRNA. 26 28 Moreover, the analytical performance of the proposed method was also compared to other reported methods (Table S2, Supporting Information ). The high sensitivity and the low background might attribute to the dual-signal amplification procedure and the high fidelity of Endo IV in specifically cleaving the TaqMan probe in dsDNA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The limit of detection (LOD) was estimated to be 0.2 pM according to the 3σ rule, which was comparable to some previously reported fluorescence assays for miRNA. 26 28 Moreover, the analytical performance of the proposed method was also compared to other reported methods (Table S2, Supporting Information ). The high sensitivity and the low background might attribute to the dual-signal amplification procedure and the high fidelity of Endo IV in specifically cleaving the TaqMan probe in dsDNA.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In 2020, Xue et al. [ 64 ] reported that ultrathin Bi nanosheets were successfully fabricated by an LPE technique in NMP solvent. The AFM topography of typical Bi nanosheets shows that the lateral dimensions of the as‐fabricated Bi nanosheets are more than 800 nm, and the thickness is quite thin (≈1 nm) ( Figure a), consistent with the previously reported bilayer thickness of Bi nanosheets.…”
Section: Synthesis Of Bi Nanostructuresmentioning
confidence: 99%
“…Reproduced with permission. [ 64 ] Copyright 2020, The Royal Society of Chemistry. d) SEM image, e) TEM image, and f) HRTEM image of Bi nanosheets prepared by in situ electrocatalytic topotactic transformation of bismuth iodide oxide nanosheets.…”
Section: Synthesis Of Bi Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations